Prophet’s Hadith Perspective on Long-Life Education: Islamic Spirit about Learning - Makuro, Vina Lailatul; Rahmania, Almaniatu Inda; Mufarroha, Lailatul; Nisak, Alfatun (PT. Riset Press International, 2025)
Lifelong education is a fundamental concept in Islam, emphasizing continuous learning of human life, from birth to death. This article discusses lifelong education according to the perspective of the Hadith of the Prophet Muhammad SAW and its implementation in the context of Islam. The formulation of the problem in this study is how the Hadith view lifelong education and what stages must be passed in such education. The method used is qualitative research with a library research approach, where data is collected through books, scientific works, and literature related to lifelong education in Islam. The results of the study show that in Islam, seeking knowledge is an obligation for every Muslim that must be carried out continuously throughout life. The stages of lifelong education in Islam include prenatal education, postnatal education, and education in adulthood, each of which has principles and objectives that are integrated to form quality individuals physically, morally, and spiritually. The implementation of this lifelong education, as explained in the Hadith of the Prophet, shows that education is a process that begins before birth and continues throughout life, ensuring that humans continue to develop in every aspect of life.